2019
DOI: 10.1080/10826084.2019.1638408
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Marijuana Use on Transitions through Stages of Alcohol Involvement for Men and Women in the NESARC I and II

Abstract: Background: With the changing context of marijuana use, it is critical to identify effects of use. We extend previous work by examining whether marijuana use influences progression and remission through alcohol involvement stages for men and women. Methods: Data come from Waves I and II of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC, n=34,432). We assess the potential influence of marijuana use at Wave 1 on transitions across three latent statuses of alcohol involvement between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Therefore, it is critical to note that co‐use still may be associated with increased risk of experiencing a consequence on certain drinking days (e.g., days with lower drinking rates). Further, this work should also be considered in the context of between‐person studies that have found a strong association between co‐use and consequences (Green et al, 2019; Midanik et al, 2007; Subbaraman & Kerr, 2015) and other within‐person studies that have found that co‐use is associated with more negative consequences compared to alcohol‐only days while controlling for alcohol consumption (Mallett et al, 2017). Finally, as discussed in our prior work (Gunn et al, 2021c; Sokolovsky et al, 2020) and work by others (Lee et al, 2020; Lipperman‐Kreda et al, 2017; Mallett et al, 2019), when alcohol use is controlled for, the association between co‐use and experience of a consequences is mitigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is critical to note that co‐use still may be associated with increased risk of experiencing a consequence on certain drinking days (e.g., days with lower drinking rates). Further, this work should also be considered in the context of between‐person studies that have found a strong association between co‐use and consequences (Green et al, 2019; Midanik et al, 2007; Subbaraman & Kerr, 2015) and other within‐person studies that have found that co‐use is associated with more negative consequences compared to alcohol‐only days while controlling for alcohol consumption (Mallett et al, 2017). Finally, as discussed in our prior work (Gunn et al, 2021c; Sokolovsky et al, 2020) and work by others (Lee et al, 2020; Lipperman‐Kreda et al, 2017; Mallett et al, 2019), when alcohol use is controlled for, the association between co‐use and experience of a consequences is mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical to note that co-use still may be associated with increased risk of experiencing a consequence on certain drinking days (e.g., days with lower drinking rates). Further, this work should also be considered in the context of between-person studies that have found a strong association between co-use and consequences (Green et al, 2019;Midanik et al, 2007;Subbaraman & Kerr, 2015) and other within-person studies that have found that co-use is associated with more negative consequences compared to alcohol-only days while controlling for alcohol consumption (Mallett et al, 2017).…”
Section: Ta B L E 5 Interaction Between Co-use and Rate On Consequencesmentioning
confidence: 99%
“…Alcohol and cannabis co-use, defined as either using both substances at the same time so that their effects overlap [simultaneous use] or being a dual user [concurrent use], is common and on the rise (e.g., Subbaraman & Kerr, 2020; Terry-McElrath & Patrick, 2018). Several cross-sectional and longitudinal studies, using predominately adolescent and young adult samples, suggest that alcohol and cannabis co-users are heavier drinkers (e.g., Haas et al, 2015; Patrick et al, 2017; Shillington & Clapp, 2006; Subbaraman & Kerr, 2015), experience more alcohol-related consequences (e.g., Green et al, 2019; Jackson et al, 2020; Linden-Carmichael, Stamates, et al, 2019; Patrick et al, 2017; Subbaraman & Kerr, 2015; Wardell et al, 2020; White et al, 2019), and are at higher risk for the development of AUD (Midanik et al, 2007) compared to alcohol-only users. Notably, in a cross-sectional study, Jackson et al (2020) found that college co-users reported more cognitive problems, vomiting, drunk driving, and overall risk behavior, and Wardell et al (2020) found that increases in cannabis use during college (when accounting for alcohol use) were associated with risky behavior, a lack of self-care, and alcohol dependence.…”
Section: Alcohol Use Cannabis Use and Alcohol And Cannabis Co-usementioning
confidence: 99%
“…These include four abuse criteria: 1) recurrent drinking resulting in a failure to fulfill major role obligations; 2) recurrent drinking in hazardous situations; 3) recurrent drinking-related legal problems; and 4) continued drinking despite recurrent interpersonal problems caused or exacerbated by drinking; and seven dependence criteria: 1) tolerance; 2) experiencing two or more withdrawal symptoms; 3) drinking larger amounts or for a longer period than intended; 4) having a persistent desire or unsuccessful attempts to cut down on drinking; 5) spending a great deal of time obtaining alcohol, drinking, or recovering from drinking’s effects; 6) giving up important social, occupational, or recreational activities in order to drink; and 7) continuing to drink despite physical or psychological problems caused by drinking. To align with the approach used in DSM-5 and prior latent class analyses ( Crum et al, 2018 , Ehlke et al, 2012 , Green et al, 2019 , La Flair et al, 2012 , La Flair et al, 2013 , Muthén, 2006 ), we considered abuse and dependence criteria together. In accordance with previous work, we selected a three-class model for both males and females based on fit statistics and parsimony in latent class analysis (see Crum et al, 2018 ): A no problem class (84.9% at Wave 1, 82.3% at Wave 2 for females; 80.7% at Wave 1, 76.1% at Wave 2 for males), a moderate problem class (12.4% at Wave 1, 14.6% at Wave 2 for females; 15.8% at Wave 1, 20.2% at Wave 2 for males), and a severe problem class (2.7% at Wave 1, 3.1% at Wave 2 for females; 3.5% at Wave 1, 3.7% at Wave 2 for males).…”
Section: Methodsmentioning
confidence: 99%